The level of students technical knowledge – survey results - NOGA, HENRYK; DEPEŠOVÁ, JANA; NESTERAK, TOMASZ; KUČERKA, DANIEL (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2016)
The necessity of the universal technical education of the youth, understood as providing themwith the basis for technical culture, is a consequence of a widespread and still growing importanceof technology in all domains of contemporary life.In the face of modern technical culture requirements, present day education cannot be limitedto acquiring manual skills. It should at the same time ensure gaining basic technical knowledgeand developing technical thinking and interests [Depešová 2011: 51–57; Piecuch 2008].Children and teenagers should be prepared to receive and apply technical knowledge in everydaylife. The grounds for that are laid by school, but it should be accompanied by other culturaland educational institutions, and by family [Depešová, Knych, Noga 2014: 59–64; Furmanek2006: 33–48; Hrmo, Kundratowa, Tinakova 2005].Forming children’s and teenagers’ technical interests is a matter of the utmost importance.Hence the necessity to coordinate the efforts of all educators in order to encourage students toacquire knowledge independently and to take an active part in an educational process organised byschool. Such a process requires from students the practical usage of mental work methods. Theknowledge about technology should systematically be updated because of a dynamic scientific andtechnical development or due to new technologies. This study shows selected survey results ofstudents’ technical knowledge on three different educational stages in Poland [Hašková, Pisoňová,Bitterová 2011; Kozík, Depešová 2007; Nazar 1973].